Physical Activity Maintenance in a Post-Cardiac Rehabilitation Population: A Mixed Methods Study - Martinello, Novella (Université d'Ottawa / University of Ottawa, 2020)
The purpose of this thesis was to better understand physical activity (PA) maintenance among patients who have completed cardiac rehabilitation (CR). Study 1: This study was a systematic review and meta-analysis of 19 randomized controlled trials (RCTs) testing PA and exercise maintenance interventions for adults who have completed CR. Descriptive synthesis of the studies combined with meta-analysis results provided evidence of increased PA among intervention groups compared with control groups at follow-up. Results of the meta-analysis found a significant difference in PA in the intervention groups compared to the control groups, via multiple exercise outcomes including exercise sessions/week (SMD = 0.20; 95% CI, 0.04 - 0.35), kcal/week (SMD = 0.59; 95% CI, 0.19 - 0.98), and daily steps (SMD = 2.14; 95% CI, 0.90 - 3.38). There is evidence to support the effectiveness of interventions aimed at maintaining PA and exercise among adults who have completed CR. Study 2: This study was a synthesis of qualitative studies examining factors affecting PA maintenance among individuals who have completed CR. Eight studies met the criteria for inclusion. Multiple factors were identified among participants, including self-efficacy and motivation, social support, support with the transition from supervised hospital or centre-based exercise to exercise in the community or home, perceived safety of the exercise program, and availability and accessibility of PA resources and opportunities. Examining qualitative literature suggests factors at the intrapersonal-, interpersonal-, organizational- and neighbourhood-level are important in supporting exercise maintenance after completion of CR. Results from this synthesis identified key areas for tailored program design, grounded in a social ecological approach. Study 3: This study was a secondary analysis of trial data examining predictors of participants’ moderate to vigorous physical activity (MVPA) 26 weeks after enrollment in a RCT of a PA maintenance intervention. Participants completed baseline questionnaires assessing social ecological, demographic, clinical, fitness, and behavioural variables. MVPA was assessed by accelerometer at baseline and 26 weeks later. Univariate analyses revealed nine significant baseline predictors of MVPA at 26 weeks including beliefs about exercise benefits, beliefs about exercise barriers, baseline MVPA, peak oxygen consumption, diabetes, age, sex, marital status, and work status. Multivariate analysis indicated that baseline MVPA was the only independent predictor of MVPA at 26 weeks. Given the pre-eminence of baseline MVPA, the regression analyses were re-run without baseline MVPA in the model. In that case, peak oxygen consumption became the only independent predictor of MVPA at 26 weeks. Results have implications for targeting intervention for PA maintenance in the unsupervised phase. Conclusion: The findings of this thesis provided insights into the influences on long-term PA among cardiac patients post-CR and the strategies which can support long-term PA. While there have been positive developments in understanding PA maintenance, there are important knowledge gaps that remain unaddressed. These knowledge gaps include the measurement, monitoring, and surveillance of PA behaviour and ways in which intervention research could be improved. Further research will be required to address these knowledge gaps and to build on the growing knowledge of effective PA interventions to support people with heart disease.
Keywords: physical activity; cardiac rehabilitation; heart disease